Millions Like Us'? : British Culture in the Second World War. - Hayes, Nick (Liverpool University Press, 1999)
This collection of essays brings together the latest historical research on cultural production and reception during the Second World War. Its starting point is how this war was presented to, and understood by, contemporaries and how they differentiated it from earlier conflicts. Although this was particularly noticeable in the construction of ideas of inclusiveness and commonality where the people pulled together to secure victory and a socially equitable peace, the essays also seek to explore the diversity of institutional and personal experiences. Essays look at major national institution.